Narrative update of clinical trials with antihypertensive drugs in children and adolescents - Redon, Josep; Seeman, Tomas; Pall, Dénes; Suurorg, Lagle; Kamperis, Konstantinos; Erdine, Serap; Wühl, Elke; Mancia, Giuseppe (Frontiers in Cardiovascular Medicine, 2022)
To date, our knowledge on antihypertensive pharmacological treatment in children and adolescents is still limited because there are few randomized clinical trials (CTs), hampering appropriate management. The objective was to perform a narrative review of the most relevant aspects of clinical trials carried out in primary and secondary hypertension and published in PubMed with the following descriptors: clinical trial, antihypertensive drug, children, adolescents. A previous Cochrane review of 21 randomized CTs pointed out the difficulty that statistical analysis could not assess heterogeneity because there were not enough data. A more recent meta-analysis, that applied more stringent inclusion criteria and selected 13 CTs, also concluded that heterogeneity, small sample size, and short follow-up time, as well as the absence of studies comparing drugs of different classes, limit the utility. In the presented narrative review, including 30 studies, there is a paucity of CTs focusing only on children with primary or secondary, mainly renoparenchymal, hypertension. In trials on angiotensin converting enzyme inhibitors (ACEI), angiotensin receptor blockers (ARBs), calcium channel blockers (CCBs) and diuretics, a significant reduction of both SBP and DBP in mixed cohorts of children with primary and secondary hypertension was achieved. However, few studies assessed the effect of antihypertensive drugs on hypertensive organ damage. Given the increasing prevalence and undertreatment of hypertension in this age group, innovative solutions including new design, such as ‘n-of-1’, and optimizing the use of digital health technologies could provide more precise and faster information about the efficacy of each antihypertensive drug class and the potential benefits according to patient characteristics.